RECONSTRUCTION OF LAW ENFORCEMENT THROUGH CAMPAIGN FINANCE TRANSPARENCY BY UTILIZING MACHINE LEARNING TO SUPPORT THE ACCOUNTABILITY OF GENERAL ELECTIONS AND REGIONAL HEAD ELECTIONS IN INDONESIA - Arya Seto Sutopo; Retno Saraswati (Awang Long Law Review, 2026)
General elections and regional elections constitute a political constellation involving various actors, including political parties, election participants, election management bodies, as well as public participation. This is constitutionally guaranteed under the Constitution of the Republic of Indonesia, particularly the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). However, this does not imply that the conduct of general elections and regional elections is free from problems. Numerous practices of corruption, vote manipulation, bribery, and the lack of transparency in campaign finance demonstrate a long-standing series of intertwined issues in electoral implementation. The preparation of this scientific paper aims to identify, analyze, and understand the problems related to campaign finance transparency and to seek ideal solutions by integrating technology through the utilization of machine learning as a decision support system. The research method employed is doctrinal legal research, with the research outcome in the form of an ideal legal formulation through legal reconceptualization. The recommendations proposed by the author include the necessity of conducting careful legal scrutiny in the form of an analysis of regulatory scope, regulatory direction, and substantive content of the proposed regulations in a comprehensive, precise, and in-depth manner. In addition, complementary synergy and coordination are required to support the supervision of campaign financing in Indonesia.